Hepatitis B viruses with precore region defects prevail in persistently infected hosts along with seroconversion to the antibody against e antigen. - Okamoto, H (1990)
The C gene of hepatitis B virus (HBV) codes for a nucleocapsid protein made of 183 amino acid residues and is preceded in phase by the precore (pre-C) region, encoding 29 residues. The pre-C-region product is required for the synthesis and secretion of hepatitis B e antigen (HBeAg), which is made of the C-terminal 10 amino acid residues of the pre-C-region product and the N-terminal 149 residues of the C-gene product. HBV mutants with pre-C-region defects prevailed in the circulation of three asymptomatic carriers as they seroconverted from HBeAg to the corresponding antibody (anti-HBe), and these mutants finally replaced nondefective HBV. HBV DNA clones were propagated from sera of an additional 15 carriers with anti-HBe and sequenced for the pre-C region. Essentially all HBV DNA clones (56 of 57 [98%]) revealed mutations that prohibited the translation of a functional pre-C-region product. A point mutation from G to A at nucleotide 83, converting Trp-28 (TGG) to a stop codon (TAG), was by far the commonest and was observed in HBV DNA clones from 16 (89%) of 18 carriers seropositive for anti-HBe. In addition, there were point mutations involving ATG codon to abort the translation initiation of the pre-C region, as well as deletion and insertion to induce frameshifts. Such mutations leading to pre-C-region defects were rarely observed in persistently infected individuals positive for HBeAg or in patients with type B acute hepatitis after they had seroconverted to anti-HBe. These results would indicate a selection of pre-C-defective mutants in persistently infected hosts, along with seroconversion to anti-HBe, by immune elimination of hepatocytes harboring nondefective HBV with the expression of HBeAg.